2021
DOI: 10.3390/ma14133550
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Microbial and Remineralizing Properties of Self-Adhesive Orthodontic Resin Containing Mesoporous Bioactive Glass

Abstract: Self-adhesive resins (SARs) contain adhesives, which simplify the procedures of resin application, and primers, which provide sufficient bonding ability. In this study, mesoporous bioactive glass nanoparticles (MBN) were added to a SAR to easily improve the physical properties and remineralization ability. The experimental resins comprised 1%, 3%, and 5% MBN mixed in Ortho Connect Flow (GC Corp, Tokyo, Japan). As the MBN content in the SAR increased, the microhardness increased, and a statistically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…A total of 20 studies [ 24 , 25 , 29 , 30 , 32 , 33 , 34 , 35 , 38 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] were found to evaluate the mechanical properties of BAG-loaded dental resin composites, where flexural strength (FS), flexural modulus (FM), biaxial flexural strength (BFS), modulus of resilience (MR), fatigue crack growth, compressive strength (CS), microhardness (MH), bond strength, and fracture toughness have mainly been analyzed ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 20 studies [ 24 , 25 , 29 , 30 , 32 , 33 , 34 , 35 , 38 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] were found to evaluate the mechanical properties of BAG-loaded dental resin composites, where flexural strength (FS), flexural modulus (FM), biaxial flexural strength (BFS), modulus of resilience (MR), fatigue crack growth, compressive strength (CS), microhardness (MH), bond strength, and fracture toughness have mainly been analyzed ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to three-point bending flexural strength, research demonstrated that a decrease of 30% in the biaxial strength is observed for Ag-containing BAG-loaded composites [ 38 ]. In addition, adding Ag- or Zn-doped BAG [ 45 ], mesoporous bioactive glass (MBG) [ 44 ], or graphene oxide-doped bioactive glass (GO-BAG) [ 49 ] to the resin adhesive enhanced the microhardness. Furthermore, resin adhesive modified with Ag- [ 45 , 47 ] or Zn-doped BAG [ 45 ] showed no significant difference in shear bond strength, compared with control resin adhesive.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations